Membangun Sistem Pengendalian Internal untuk Menanggulangi Resiko Fraud di Perusahaan - Jennie Aurellia Zaneta (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article discusses the development of an internal control system as an effort to overcome the risk of fraud in the company. Through in-depth analysis of existing policies, procedures and practices, this research identifies key elements that can strengthen organizational integrity. Using a case study approach, this article shows how implementing effective controls, employee training, and reporting mechanisms can increase transparency and accountability. The results of this research conclude that a comprehensive internal control system not only reduces the risk of corruption, but also encourages an ethical culture in the work environment, thereby supporting the company's sustainability and reputation.